'If he feels better I'll feel better' relationships with individuals at high‐risk of developing psychosis. Issue 3 (24th March 2021) - Izon, Emma; Berry, Katherine; Law, Heather; French, Paul
Abstract: Aim: A large proportion of individuals with an at‐risk mental state (ARMS) live at home and are supported by their families. Recommended treatment includes family intervention (FI), and therefore, understanding relationships between individuals with an ARMS and their family members is key. This study aimed to provide a more holistic exploration of relationships within families of individuals with an ARMS by reporting the perceived impact of the condition on other family members including sibling and romantic relationships. Method: Fourteen semi‐structured interviews with family members were analysed using thematic analysis. Results: Parents wanted to maintain a safe family environment for all family members. This can result in spending less time with siblings who impacted on siblings' relationships with the service user and other family members. Romantic relationships were negatively impacted when there was unclear communication between the couple, as well as the partner's response and understanding of the ARMS condition. Clear communication across sibling and romantic relationships facilitated helpful family/carer's behaviour and understanding of the individuals' mental distress. Conclusion: FI should explore and support families with changes in sibling and romantic relationships. More research is needed to understand siblings' perspectives in families with individuals experiencing an ARMS and to develop resources to support partners and families in changes within their sexual and romantic relationships.